PENGARUH IMPLEMENTASI TATA KELOLA SEKTOR PUBLIK YANG BAIK TERHADAP KUALITAS ANGGARAN SKPD - Firma Sulistiyowati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The good financial management of local government related to good public governance. The good public governance will encourage the good financial statement in local government, including the quality of Satuan Kerja Perangkat Daerah (SKPD) budget. The aim of this research is to examine the influence of implementation good public governance upon the quality of SKPD budget. This research uses a quantitative approach with survey method. The data was gathered by questionnaire. The number of respondents in the research are 430 public servants (ASN) in Kabupaten/Kota/Provinsi Daerah Istimewa Yogyakarta (DIY), including Kabupaten Sleman, Kabupaten Bantul, Kabupaten Kulonprogo, Kabupaten Gunung Kidul, Pemerintah Kota Yogyakarta, and Pemerintah Provinsi DIY. The Techniqe of data analysis was used in this study is simple regression. The simple regression is a tool to analyze the effect of independent variable (implementation of good public governance) towards dependent variable (the quality of SKPD budget). The result of this study shows that the implementation of good public governance in Kabupaten/ Kota/Provinsi DIY influences the quality of SKPD budget.